ENTREPRENEURIAL BEHAVIOR OF MSME ACTORS IN THE CASSAVA PROCESSING SECTOR: A CASE STUDY OF PADANG CITY - Reza Mardhiyah Amir; Annisa Ulhusna; Pinta Aftaprilia Rizki Ananda (Universitas Muhammadiyah Sidenreng Rappang, 2025)
This study aims to analyze the entrepreneurial behaviors of MSME actors in the cassava processing sector in Padang City and their influence on business performance. A descriptive quantitative approach was employed, with data collected through interviews and a 5-point Likert scale questionnaire distributed to cassava processing entrepreneurs. The results indicate that individual factors such as education, experience, and motivation are categorized as high and positively contribute to entrepreneurial behavior. Environmental factors such as input availability, training, capital assistance, promotion, and the cohesiveness among entrepreneurs also support business performance, although challenges remain in extension services, marketing, and business regulations. Overall, the business performance of cassava processing MSMEs in Padang City is classified as high, as reflected in market expansion, increased income, and competitive advantage. The synergy between strong individual characteristics and optimal environmental support is key to enhancing the competitiveness and sustainability of cassava processing businesses in Padang City. Keywords: Business performance; Cassava, Entrepreneurial; Entrepreneurial behavior; MSMEs